Decoding the secrets of longevity: unraveling nutraceutical and miRNA-Mediated aging pathways and therapeutic strategies - Salama, Rania M.; Eissa, Nermin; Doghish, Ahmed S.; Abulsoud, Ahmed I.; Abdelmaksoud, Nourhan M.; Mohammed, Osama A.; Abdel Mageed, Sherif S.; Darwish, Samar F. (Frontiers in Aging, 2024)
MicroRNAs (miRNAs) are short RNA molecules that are not involved in coding for proteins. They have a significant function in regulating gene expression after the process of transcription. Their participation in several biological processes has rendered them appealing subjects for investigating age-related disorders. Increasing data indicates that miRNAs can be influenced by dietary variables, such as macronutrients, micronutrients, trace minerals, and nutraceuticals. This review examines the influence of dietary factors and nutraceuticals on the regulation of miRNA in relation to the process of aging. We examine the present comprehension of miRNA disruption in age-related illnesses and emphasize the possibility of dietary manipulation as a means of prevention or treatment. Consolidating animal and human research is essential to validate the significance of dietary miRNA control in living organisms, despite the abundance of information already provided by several studies. This review elucidates the complex interaction among miRNAs, nutrition, and aging, offering valuable insights into promising areas for further research and potential therapies for age-related disorders.